2019
DOI: 10.1088/1742-6596/1246/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of monocytes to lymphocytes accuracy as tuberculosis predictor

Abstract: Tuberculosis is one of the top ten death’s causes in the world and even cause more deaths than HIV in 2015. In the same years, there are 10.4 million new TB case incidences with case notification rate is 142/100,000 population globally. Monocytes and lymphocytes play an important role in the body’s defense mechanism against tuberculosis. Tuberculosis can induce increased monocytes and decreased lymphocytes. The ratio of Monocytes to lymphocytes is expected to be used as predictors of tuberculosis. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[6] A total of 15 studies were included in this systematic review and meta-analysis to investigate the accuracy of MLR for the diagnosis of TB and also its role in monitoring anti-TB therapy. [22] Egypt 50 50 0.46 ± 0.30 0.15 ± 0.06 80 90 Ngahane et al 2019 [24] Cameroon 204 204 0.39 ± 0.23 0.19 ± 0.11 67.2 83.3 Manna et al 2017 [3] Italy 31 71 0.50 ± 0.20 0.18 ± 0.06 91.04 93.55 Liana et al 2019 [23] Indonesia 41 60 0.97 ± 0.51 0.57 ± 0.76 95.1 70 Rakotosamimanana et al 2015 [20] Madagascar 85 186 --4.97 (1.3-18.99) Rees et al 2020 [26] Tanzania 98 47 --68 51 Choudhary et al 2019 [18] Kenya 13 67 0.48 ± 0.3 0.23 ± 0.2 77 78 Naranbhai et al2014 [17] South Africa* 12 1190 --1.22 (1.07-1.4) Naranbhai et al2014 [11] South Africa 1862 --2.47 (1.39-4.40) Ginderdeuren et al 2021 [19] South Africa 51 120 0.22 ± 0.16 0.34 ± 0.27 0.78 (0.59, 0.97) Naranbhai et al2014 [12] South Africa 1336 -1.23 (1.04-1.45) MLR before treatment MLR after treatment Wang et al 2015 [8] China 419 327 0.47 ± 0.21 0.22 ± 0.09 Iqbal et al 2014 [21] Pakistan 45 45 0.24 ± 0.14 0.19 ± 0.10 Okeke et al 2020 [25] Nigeria 60 60 0.11 ± 0.08 0.08 ± 0.06 Wang et al 2019 [9] China 151 129 0.47 ± 0.29 0.34 ± 0.5 In this study, a significant increase in MLR was observed among TB patients compared to controls (SMD = 0.69; 95% CI, 0.37-1.01). It has been reported that circulating monocytes from patients with TB exhibit phenotypic and functional alterations compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] A total of 15 studies were included in this systematic review and meta-analysis to investigate the accuracy of MLR for the diagnosis of TB and also its role in monitoring anti-TB therapy. [22] Egypt 50 50 0.46 ± 0.30 0.15 ± 0.06 80 90 Ngahane et al 2019 [24] Cameroon 204 204 0.39 ± 0.23 0.19 ± 0.11 67.2 83.3 Manna et al 2017 [3] Italy 31 71 0.50 ± 0.20 0.18 ± 0.06 91.04 93.55 Liana et al 2019 [23] Indonesia 41 60 0.97 ± 0.51 0.57 ± 0.76 95.1 70 Rakotosamimanana et al 2015 [20] Madagascar 85 186 --4.97 (1.3-18.99) Rees et al 2020 [26] Tanzania 98 47 --68 51 Choudhary et al 2019 [18] Kenya 13 67 0.48 ± 0.3 0.23 ± 0.2 77 78 Naranbhai et al2014 [17] South Africa* 12 1190 --1.22 (1.07-1.4) Naranbhai et al2014 [11] South Africa 1862 --2.47 (1.39-4.40) Ginderdeuren et al 2021 [19] South Africa 51 120 0.22 ± 0.16 0.34 ± 0.27 0.78 (0.59, 0.97) Naranbhai et al2014 [12] South Africa 1336 -1.23 (1.04-1.45) MLR before treatment MLR after treatment Wang et al 2015 [8] China 419 327 0.47 ± 0.21 0.22 ± 0.09 Iqbal et al 2014 [21] Pakistan 45 45 0.24 ± 0.14 0.19 ± 0.10 Okeke et al 2020 [25] Nigeria 60 60 0.11 ± 0.08 0.08 ± 0.06 Wang et al 2019 [9] China 151 129 0.47 ± 0.29 0.34 ± 0.5 In this study, a significant increase in MLR was observed among TB patients compared to controls (SMD = 0.69; 95% CI, 0.37-1.01). It has been reported that circulating monocytes from patients with TB exhibit phenotypic and functional alterations compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, having a simple and rapid predictor to distinguish TB patients from healthy control and/or non-TB patients is very useful. [23] Although several biomarkers are available for diagnosing and monitoring TB, they are quite expensive and are not friendly in countries with a high burden of the disease. This in turn causes delays in diagnosis that exacerbate the patient's morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences among the studies are probably related to the characteristics of the study subjects. La Manna et al 24 compared healthy patients and TB patients, while Liana et al 21 compared patients with chronic cough and positive and negative bacterial cultures. Elevated lymphocyte counts are controversial in patients without mycobacterial isolation, and they indicate a better immune response against infection, resulting in larger granulomas with fewer bacilli, thus affecting mycobacterial isolation.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Laboratorial: leukocytes, monocyte/lymphocyte ratio, C-reactive protein and erythrocyte sedimentation rate. 11,[19][20][21] Imaging tests: number of affected levels, multiple levels, non-contiguous levels, location (cervical, thoracic, thoracolumbar transition and lumbar -we considered lesions in more than one region, as is the case with non-contiguous lesions, as more than one). 10,22,23 Microbiological: anatomopathological (hematoxylin-eosin staining, presence of granuloma with caseous necrosis), bacilloscopy (Ziehl-Neelsen staining, alcohol-acid resistant bacilli research), culture (Löwenstein-Jensen medium) and RMT-TB (GeneXpert MTB/RIF method).…”
Section: Methodsmentioning
confidence: 99%